2017
DOI: 10.3390/ijms18102040
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of CCA1-Like Proteins in Soybean and Functional Characterization of GmMYB138a

Abstract: Plant CIRCADIAN CLOCK ASSOCIATED1 (CCA1)-like proteins are a class of single-repeat MYELOBLASTOSIS ONCOGENE (MYB) transcription factors generally featured by a highly conserved motif SHAQK(Y/F)F, which play important roles in multiple biological processes. Soybean is an important grain legume for seed protein and edible vegetable oil. However, essential understandings regarding CCA1-like proteins are very limited in soybean. In this study, 54 CCA1-like proteins were identified by data mining of soybean genome.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…A CCA1 -like MYB protein, GmMYB138a, interacts with GmSGF14l (a 14-3-3 protein) that alters the subcellular localization of GmMYB138a. qPCR analysis demonstrated that GmMYB138a and GmSGF14l respond synergistically or antagonistically to salt, drought, and cold stresses [ 220 ]. In addition, Jaradat et al [ 206 ] stated that Arabidopsis MYBR1 physically interacts with an ABA receptor protein, PYL8, and directly participates in early ABA signaling.…”
Section: Potential Molecular Mechanisms Of Tfs In Controlling Planmentioning
confidence: 99%
“…A CCA1 -like MYB protein, GmMYB138a, interacts with GmSGF14l (a 14-3-3 protein) that alters the subcellular localization of GmMYB138a. qPCR analysis demonstrated that GmMYB138a and GmSGF14l respond synergistically or antagonistically to salt, drought, and cold stresses [ 220 ]. In addition, Jaradat et al [ 206 ] stated that Arabidopsis MYBR1 physically interacts with an ABA receptor protein, PYL8, and directly participates in early ABA signaling.…”
Section: Potential Molecular Mechanisms Of Tfs In Controlling Planmentioning
confidence: 99%
“…These are accompanied by many physiological, biochemical and developmental changes [2]. Current research on plant stress response has reached the level of cells and molecules, and combined with genetics, we can explore the stress responsive mechanisms in order to improve plant growth under conditions of stress [3,4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The species of MYB-related TF genes were various in different species (Table 1 ). To analyze the entire MYB-related family in soybean, we queried several databases such as Phytozome, TFDB, Pfam, SMART and ScanProsite [ 10 ]. Previous work revealed 127 MYB-related TF genes in soybean [ 28 ]; and these genes were searched against the above websites.…”
Section: Resultsmentioning
confidence: 99%
“…According to the gene accession number we submitted to the soybase website ( http://soybase.org/soyseq/ ) [ 10 ], we obtained the tissue expression data of quantified prediction for a diverse set of fourteen tissue types (Additional file 1 : Figure S1). It showed that the expression level of several genes in roots, leaf nodes, leaves and flowers was higher than that in seeds and pods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation